Leadership in health care - Barr, Jill.; Dowding, Lesley (Los Angeles : SAGE, 2012)
'Leadership In Health Care' is an authoritative and timely book that addresses the need for leading skilled and evidence-based care within the context of a performance-measured health service--
Pt. 3. The organisation : 11. Theory of organisational life : What is the purpose of an organisation? ; Strategy, structure and systems ; Strategy ; Rational strategy ; Emergent strategies ; Vision, mission and goals ; Leadership and health policy ; Changing government strategy ; Public health, health promotion and policy ; Involvement in the policy-making process ; Structure ; Types of structures ; Organisational roles ; Accountability, responsibility, authority and delegation ; Accountability to the public ; Duty of care ; Employment accountability ; Organisational culture ; Health service systems ; Human resource management (HRM) ; Induction of new staff ; Training and development and the NHS framework for skills and knowledge -- 12. Quality : Historical context of quality movement in health care ; Total quality management (TQM) ; Concept of quality ; Models of quality in the health service ; Clinical governance ; Clinical audit ; Clinical effectiveness ; The NHS performance assessment framework ; Health equity and health equality ; Clinical risk management ; Quality assurance ; Staff development ; Professional development and clinical supervision ; Accountability and quality -- 13. Leadership for change : Defining change ; Theories of change management ; The leader as an instrument of change ; The process of change ; Response to change ; Leading the team through change ; Successful vs unsuccessful change ; Unplanned change ; Planned change ; Experiences for successful change ; Project management ; Planning for change ; Action learning sets -- 14. Conclusions : Rumof chapters ; Leading health care in the future.
Includes bibliographical references ([277]-292) and index.
Keywords: Health services administration; Nursing services -- Administration; Health Services Administration; Interprofessional Relations; Leadership